2014
DOI: 10.1186/1471-2415-14-128
|View full text |Cite
|
Sign up to set email alerts
|

Time trend of prevalence of self-reported cataract and its association with prolonged sitting in Taiwan from 2001 and 2013

Abstract: BackgroundProlong sitting has been found associated with metabolic disorders. Little is known about the self-reported cataract status in general population of Taiwan, not to mention its relation to prolong sitting. We aimed to examine the prevalence of cataract between 2001 and 2013 in Taiwan and to the association between prolonged sitting and cataract.MethodsWe used three data sets with those aged 40 years and older from the National Health Interview Survey (NHIS) from 2001 (n = 8334), 2009 (n = 11207), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
5
18
2
Order By: Relevance
“…In line with many previous studies [ 29 31 ], cataract was more common in women than men, with the prevalence of 6.41% versus 3.51% in the present study. Such difference is often addressed by the estrogen deficiency [ 10 ] or biomass cooking fuels [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…In line with many previous studies [ 29 31 ], cataract was more common in women than men, with the prevalence of 6.41% versus 3.51% in the present study. Such difference is often addressed by the estrogen deficiency [ 10 ] or biomass cooking fuels [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…[3] The occurrence rate of sight-threatening cataract in the study group is approximately 27.9 percent which was three-folds higher than the 8.4 percent in the DM control group and the 7.3 percent in the non-DM control group. In a previous population-based study conducted in the same region, the prevalence of self-reported cataract was about 11.8 percent in 2013, [37] which was much lower than the study group in the current study. Since both DM and cataract affect a majority of population and the DR will increase the risk of sight-threatening cataract with a gross population, strictly blood sugar control and periodically ophthalmic examination in patients with DM is advocated.…”
Section: Discussioncontrasting
confidence: 72%
“…Rural residents are exposed to higher levels of ultra-violet radiation than their urban counterparts [ 3 ]. A recent study of population at age 40 years and older in Taiwan proper showed that the prevalence of cataracts as indicated by medical professionals (excluding mild cataracts) was 11.8 % [ 36 ]. The prevalence of moderate and severe cataracts in Matsu (13.9 %, 117/841) was consistent with this previous study, as we investigated residents aged 50 years and older.…”
Section: Discussionmentioning
confidence: 99%